Discover a world of knowledge at Westonci.ca, where experts and enthusiasts come together to answer your questions. Join our platform to connect with experts ready to provide accurate answers to your questions in various fields. Discover detailed answers to your questions from a wide network of experts on our comprehensive Q&A platform.

Drag the tiles to the boxes to form correct pairs.

Consider functions [tex]f[/tex] and [tex]g[/tex]:

[tex]
\begin{array}{l}
f(x) = 1 - x^2 \\
g(x) = \sqrt{11 - 4x}
\end{array}
[/tex]

Evaluate each combined function, and match it to the corresponding value.

[tex]\sqrt{3} - 3[/tex]
[tex]\sqrt{15}[/tex]
[tex]-3 \sqrt{3}[/tex]
[tex]0[/tex]

[tex]
\begin{array}{l}
\left(\frac{f}{g}\right)(-1) \longrightarrow \\
(g+f)(2) \longrightarrow \\
(g-f)(-1) \longrightarrow \\
(g \cdot f)(2) \longrightarrow \\
\end{array}
[/tex]


Sagot :

To evaluate each combined function and match it to the corresponding value, let's look at each function step-by-step:

1. Evaluate [tex]\(\left(\frac{f}{g}\right)(-1)\)[/tex]:
[tex]$ f(x) = 1 - x^2 $[/tex]
[tex]$ f(-1) = 1 - (-1)^2 = 1 - 1 = 0 $[/tex]

[tex]$ g(x) = \sqrt{11 - 4x} $[/tex]
[tex]$ g(-1) = \sqrt{11 - 4(-1)} = \sqrt{11 + 4} = \sqrt{15} $[/tex]

[tex]$ \left(\frac{f}{g}\right)(-1) = \frac{f(-1)}{g(-1)} = \frac{0}{\sqrt{15}} = 0 $[/tex]

The combined function [tex]\(\left(\frac{f}{g}\right)(-1)\)[/tex] corresponds to [tex]\(0\)[/tex].

2. Evaluate [tex]\((g + f)(2)\)[/tex]:
[tex]$ f(2) = 1 - 2^2 = 1 - 4 = -3 $[/tex]

[tex]$ g(2) = \sqrt{11 - 4(2)} = \sqrt{11 - 8} = \sqrt{3} $[/tex]

[tex]$ (g + f)(2) = g(2) + f(2) = \sqrt{3} - 3 $[/tex]

The combined function [tex]\((g + f)(2)\)[/tex] corresponds to [tex]\(\sqrt{3} - 3\)[/tex].

3. Evaluate [tex]\((g - f)(-1)\)[/tex]:
We've already found [tex]\( f(-1) = 0 \)[/tex] and [tex]\( g(-1) = \sqrt{15} \)[/tex].

[tex]$ (g - f)(-1) = g(-1) - f(-1) = \sqrt{15} - 0 = \sqrt{15} $[/tex]

The combined function [tex]\((g - f)(-1)\)[/tex] corresponds to [tex]\(\sqrt{15}\)[/tex].

4. Evaluate [tex]\((g \cdot f)(2)\)[/tex]:
We've already found [tex]\( f(2) = -3 \)[/tex] and [tex]\( g(2) = \sqrt{3} \)[/tex].

[tex]$ (g \cdot f)(2) = g(2) \cdot f(2) = \sqrt{3} \cdot (-3) = -3\sqrt{3} $[/tex]

The combined function [tex]\((g \cdot f)(2)\)[/tex] corresponds to [tex]\(-3\sqrt{3}\)[/tex].

Putting it all together, we get the following pairs:

[tex]\[ \begin{array}{ll} \left(\frac{f}{g}\right)(-1) & \longrightarrow 0 \\ (g + f)(2) & \longrightarrow \sqrt{3} - 3 \\ (g - f)(-1) & \longrightarrow \sqrt{15} \\ (g \cdot f)(2) & \longrightarrow -3\sqrt{3} \\ \end{array} \][/tex]